2010
DOI: 10.1210/er.2009-0030
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota, Lipopolysaccharides, and Innate Immunity in the Pathogenesis of Obesity and Cardiovascular Risk

Abstract: Compelling evidence supports the concepts that gut microbiota actively promotes weight gain and fat accumulation and sustains, indirectly, a condition of low-grade inflammation, thus enhancing the cardiovascular risk. Fewer Bacteroidetes and more Firmicutes seem to characterize the gut microbiota of obese people as compared with that of lean individuals. This difference translates into an increased efficiency of microbiota of obese individuals in harvesting energy from otherwise indigestible carbohydrates. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
323
0
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 413 publications
(339 citation statements)
references
References 243 publications
5
323
0
11
Order By: Relevance
“…25 In animal models lowgrade 'metabolic' endotoxemia has been described as a key factor in weight gain, insulin resistance and low-grade inflammation. 26 However, in our study we could not detect endotoxin in peripheral blood of any of the patients with MetS although we used an optimized endotoxin test. 27 The reason why we could not detect endotoxin in the serum of our subjects could be that the metabolic and inflammatory processes of MetS were not advanced enough in our patient cohort to cause detectable endotoxin levels in the circulation.…”
Section: Discussionmentioning
confidence: 69%
“…25 In animal models lowgrade 'metabolic' endotoxemia has been described as a key factor in weight gain, insulin resistance and low-grade inflammation. 26 However, in our study we could not detect endotoxin in peripheral blood of any of the patients with MetS although we used an optimized endotoxin test. 27 The reason why we could not detect endotoxin in the serum of our subjects could be that the metabolic and inflammatory processes of MetS were not advanced enough in our patient cohort to cause detectable endotoxin levels in the circulation.…”
Section: Discussionmentioning
confidence: 69%
“…Likewise, a recent cross-sectional study in 420 Spanish individuals also indicated that higher LBP was associated with MetS and its components, including central obesity and low HDL-cholesterol [12]. However, the cross-sectional nature of previous studies could lead to reverse causation, since common symptoms of MetS may also alter gastrointestinal conditions and promote occurrence of subclinical endotoxaemia [10,11]. With a prospective design, our current analyses provided stronger evidence to support the putative contributions of endotoxaemia to the development of metabolic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the components of MetS, such as hypertriacylglycerolaemia, hyperglycaemia and hyperinsulinaemia, have been hypothesised to contribute to endotoxaemia through altering jejunal motility and gastrointestinal transit time, conditions that may favour bacterial overgrowth and leak endotoxins into the intestinal mucosa [10,11]. Whether endotoxaemia predisposes to the onset of metabolic deterioration in free-living populations remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon, which extends to perinatal and postnatal age, is known as disease programming during the development phase (46). Indeed, it is known that the gut microbiota has an effect on the individual risk to develop diseases in adulthood, especially in case of cardiovascular diseases, as a result of weight gain, fat accumulation, and maintenance of a basic mild inflammation condition (47). In addition, epidemiological studies on human populations have shown some associations between neurological development Figure 2.…”
Section: Dysbiosis Progression Of Gut Microbiota: a Prediction Tool Omentioning
confidence: 99%